Morphometric Analysis of Gender-affirming Breast Augmentation. Issue 11 (29th November 2022) - Song, Siyou; Parmeshwar, Nisha; Steiner, Gabriela; Kim, Esther A.
Abstract : Background: According to cisgender respondents, the "preferred" feminine breast has a 45:55 upper-to-lower pole ratio. Preferred breast ratios have not been evaluated for transgender women undergoing breast augmentation. Therefore, this study aimed to determine the preferred breast ratio according to the transgender population and, thus, better inform surgeon planning. Methods: Patients diagnosed with gender dysphoria were sent a survey with morphed breast images of four different upper-to-lower pole ratios: 35:65, 45:55, 50:50, and 55:45. Respondents ranked the images according to aesthetic preference. Rankings were analyzed by the Condorcet method. Results: 298 survey responses were analyzed: 197 (66.1%) respondents identified as transgender women and 31 (10.4%) as transgender men. Most respondents were younger than 40 (64.8%). Eighty-one (27.2%) had undergone breast augmentation, 136 (45.6%) had not and were not considering it, and 81 (27.2%) had not but were considering it. Across all subgroups, the most preferred ratio was 45:55 ( P = 0.046). Those with more masculine genders and assigned female at birth preferred the 45:55 and 50:50 ratios equally. Those in their 30's and younger preferred the 45:55 and 50:50 ratios equally. Conclusions: The 45:55 ratio, established as the most preferred morphometrics for breast augmentation by cisgender respondents, is also the most aesthetically preferred proportion among transgender patients. Interestingly, the 50:50 ratio, which projects a larger upper bust compared to the 45:55 ratio, may be equally or more appealing to younger patients and those with more masculine genders. We hope these results improve patient-physician shared decision-making and postoperative expectations.